Testing the trade credit and trade link: Evidence from data on export credit insurance - Marc Auboin; Martina Engemann (World Trade Organization (WTO), 2012)
Trade finance has received special attention during the financial crisis as one of the potential culprits for the great trade collapse. Several researchers have used micro level data to establish the link between trade finance and trade, especially so during the financial crisis, and have found diverting results. This paper analyses the effect of trade credit on trade on a macro level through a whole cycle. We employ Berne Union data on export credit insurance, the most extensive dataset on trade credits available at the moment, for the period of 2005-2011. Using an instrumentation strategy we can identify a significantly positive effect of insured trade credit, as a proxy for trade credits, on trade. The effect of insured trade credit on trade is very strong and remains stable over the cycle, not varying between crisis and non-crisis periods.
Keywords: F13; F34; G21; G23; 330; trade credit; financial crisis; import estimation; Außenhandelsfinanzierung; Finanzkrise; Exportkredit; Exportkreditversicherung